Radio frequency interference pocket guide : RFI characterization, location techniques, tools and remediation methods, with key equations and data - Wyatt, Kenneth (Product development engineer); Gruber, Michael (Electromagnetics and radar, 2015)
The book discusses on Radio Frequency Interference (RFI) characterization, location techniques, tools and remediation methods, with key equations and data.